LAND COVER MAPPING DETAILS USE UNMANNED AERIAL VEHICLE IN RIAU UNIVERSITY ARBORETUM AND SURROUNDING - Wahyu Bintoro; Yossi Oktorini; Viny Volcherina Darlis (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2018)
Unmanned aerial vehicle is one way to get the information of spatial data that photographed in detail small objects on the land with coverage area that is not too broad. The photo shoot was done in the Riau University Arboretum and surrounding areas. The location of the photo shoot on the research including scientific development zone to study forest ecosystems, activities of Student Affairs and the place that usually visited by community. This research aims to mapping and to know the land cover in the Riau University Arboretum and to know value of the accuracy test of the aerial photography from the unmanned aerial vehicle. The aerial photography is analyzed by visual interpretation, the maximum scale based on spatial resolution and use omission commission testing accuracy to compare the value of the observed object in the field and aerial photograph. The bounderies of Riau University Arboretum is not in the field physically, so the Riau University Arboretum as a landmark. The result of the maximum scale is 1:100 with 2.77 cm spatial resolution, so it seems clear the land cover in the aerial photography i.e. vegetation, buildings, and undeveloped land. The result of accuracy test that was conducted showed that the percentage of accuracy reaches 95%, so that the data from the unmanned aerial vehicle can be utilized for mapping a region.